Aristotle and the problem of forgiveness - Carter, J (Philosophy Documentation Centre, 2017)
In recent decades, it has been argued that the modern concept of forgiveness is absent from Aristotle’s conception of συγγνώμη as it appears in his Rhetoric and Nicomachean Ethics. In this paper, I argue that Aristotle’s view is more modern than it might appear. I defend the idea that Aristotle’s treatment of συγγνώμη, when seen in conjunction with his theory of ethical decision, involuntary action, and character alteration, commits him to a cognitive and emotional theory of forgiveness that is both well grounded, and thoroughly modern. I go on to claim that Aristotle’s view of συγγνώμη helps to solve at least four controversial problems about the nature of forgiveness raised by modern philosophers: how one can forgive a wrong without condoning it, whether forgiveness is a duty, whether moral luck requires us to forgive more widely, and whether forgiveness ought to be unconditional.